Biomass Valorization via Paired Electrosynthesis Over Vanadium Nitride‐Based Electrocatalysts. (15th August 2019) - Li, Suiqin; Sun, Xiang; Yao, Zihao; Zhong, Xing; Cao, Yongyong; Liang, Yulin; Wei, Zhongzhe; Deng, Shengwei; Zhuang, Guilin; Li, Xiaonian; Wang, Jianguo
Abstract: Paired electrosynthesis is a promising technology with the potential to generate value‐added products at both electrodes in a cost‐effective manner. Herein, 3D vanadium nitride (VN) and Pd/VN hollow nanospheres are successfully fabricated and coupled to carry out simultaneous electrocatalytic oxidation (ECO) and electrocatalytic hydrogenation (ECH) of 5‐hydroxymethylfurfural (HMF) into 2, 5‐furandicarboxylic acid (FDCA) and 2, 5‐bishydroxymethyl‐tetrahydrofuran (DHMTHF), respectively. VN shows excellent ECO performance with high HMF conversion (≥98%), FDCA selectivity (≥96%), and faradaic efficiency (≥84%) after a stability test, and Pd/VN achieves high ECH selectivity for DHMTHF at ≥88% and an HMF conversion of ≥90%, with a faradaic efficiency of ≥86%. VN and Pd/VN incorporated into a membrane electrode assembly in a paired electrolysis system shows potential for large‐scale biomass conversion and upgrading. Theoretical calculations reveal that the higher performance of VN for the production of ECO can be attributed to its lower d‐band center level relative to the Fermi level compared to that of V2 O5, which favors HMF chemisorption and activation. This study paves the way for developing paired electrosynthesis technologies with the potential for biomass utilization and energy conversion. Abstract : A paired electrolysis system is employed for simultaneous electrocatalytic oxidation of 5‐hydroxymethylfurfural to 2, 5‐furandicarboxylic acid and electrocatalytic hydrogenation to 2, 5‐bishydroxymethyl‐tetrahydrofuran using VN and Pd/VN as electrocatalysts with excellent activity. This strategy opens up a new avenue for biomass utilization and energy conversion.